Describing the Delivery of Evidence-Based Physical Therapy Intervention to Individuals With Cerebral Palsy. Issue 2 (April 2021) - Bailes, Amy F.; Greve, Kelly; Long, Jason; Kurowski, Brad G.; Vargus-Adams, Jilda; Aronow, Bruce; Mitelpunkt, Alexis
Abstract : Purpose: To characterize by evidence grades and examine variation in type of physical therapy intervention delivered in routine clinical care in individuals with cerebral palsy (CP). Methods: Retrospective data collection from the electronic record over 1 year at a tertiary care pediatric outpatient therapy division. Results: Four hundred sixty-five individuals with CP received 28 344 interventions during 4335 treatment visits. Sixty-six percent of interventions were evidence-based interventions (EBIs). Significant variation was demonstrated across Gross Motor Function Classification System levels, with children classified as level V receiving the least and level III the most. The most frequent EBIs delivered were caregiver education, motor control, functional strengthening, ankle-foot orthoses, treadmill training, and fit of adaptive equipment. Conclusions: Further work is needed to determine whether amount of EBI is related to better outcomes. Combining this information with other aspects of dose (intensity, time, and frequency) may elucidate the contribution of each with outcomes. Abstract : Supplemental Digital Content is Available in the Text.The purpose of this study was to characterize the type of physical therapy intervention delivered in routine clinical care in a large sample of children with CP, and to examine variation by age, Gross Motor Function Classification System, race, and insurance type.